Metabolomics Profiles of Solid State and Submerge Fermentation of Corn Silk using Mixed Microbes - Wuttiyan, Watchapon; Changtor, Phanupong; Pooam, Marootpong; luangpipat, Tiyaporn; Urit, Thanet; Chaijamrus, Sirilux (Trends in Sciences, 2024)
Corn silk is a waste product when harvesting corn, but it contains many bioactive compounds. This research characterized and assessed the antioxidant bioactivity of compounds isolated from corn silk. Two different biological fermentation processes were compared: Solid-state fermentation (SSF) and submerged fermentation (SmF). Fresh corn silk (Zea mays L.) from both sweet corn and feed corn were fermented separately with various microorganisms (Bacillus subtilis, Lactobacillus sp. and Saccharomyces cerevisiae). Biological compounds were identified using LC-MS/MS. The extract was then tested for total phenolic content (TPC) and total flavonoid content (TFC). Next, the extract was tested for xanthine oxidase inhibition and antioxidant inhibition using the ABTS method. Potential contamination with the heavy metals As, Pb, and Hg was checked. The results show that fermented corn silk extract contains numerous bioactive compounds and amino acids. Among the different extract process variations, the highest TPC and TFC were 6.1 ± 0.7 µg GAE/g dry wt. and 68.3 ± 1.1 µg QE/g dry wt., respectively, and the highest xanthine oxidase inhibition was 76.5 ± 6.4 %. The above highest results were obtained using SmF of sweet corn for 60 days. In contrast, the highest antioxidant activity of 66.9 % was found using SSF of sweet corn for 20 days. Neither sweet corn nor feed corn were found to contain heavy metal ions. In summary, fermented corn silk extract samples contain numerous bioactive compounds, including both flavonoid and phenolic compounds, and the extract demonstrates antioxidant activity. Corn silk extracts from fermentation thus have potential for utilization in health products. HIGHLIGHTS Feed corn silk and sweet corn silk underwent solid-state fermentation (SSF) or submerged fermentation (SmF) for extraction using heterofermentative microbes of Bacillus subtilis, Lactobacillus and Saccharomyces cerevisiae to produce the high bioactive compounds, amino acids, and organic acids Metabolomic analysis of the fermentation extracts was carried out by LC-ESI-QTOF-MS/MS (Liquid Chromatography-Mass Spectrometry) using the heatmaps generated metabolites profiles The main amino acids found in the extractions were phenylalanine, leucine, and their derivatives SmF of sweet corn silk yielded the highest xanthine oxidase inhibitory activity (76 %) SSF of feed corn silk and sweet corn silk displayed the high antioxidant activity GRAPHICAL ABSTRACT